Heterocycle‐Tethered Aurones: Synthesis and Evaluation of α‐Glucosidase Inhibition. - Kobzar, Oleksandr L.; Popova, Antonina V.; Bondarenko, Svitlana P.; Mrug, Galyna P.; Vovk, Andriy I.; Frasinyuk, Mykhaylo S.; Gencer, Nahit (BioMed Research International, 2026)
A wide range of heterocycle‐tethered aurones were synthesized using an efficient approach for the capture of in situ generated aurone‐based ortho‐quinone methide intermediates by 3‐(2‐hydroxyphenyl)enaminones and further ring‐opening and ring‐closure reaction with bidentate nucleophiles. The synthesized compounds were investigated in vitro as inhibitors of Saccharomyces cerevisiae α‐glucosidase. The activity of the methylene‐linked heterocycle‐aurone hybrids with substituted pyrazole or isoxazole moieties was found to be similar to that of chromone‐aurones and significantly exceeded the activity of corresponding aurones with pyrimidine or pyrazolo[1,5‐a]pyrimidine fragments. The azole‐aurone compounds can exhibit high inhibitory potency towards α‐glucosidase with IC50 values ranging from 3.0 ± 0.8 to 23.2 ± 5.1 μM, being much more active than acarbose with an IC50 value of 760 ± 120 μM. According to the results of kinetic studies, these compounds were found to be mixed‐type inhibitors, affecting enzyme activity through multiple binding sites, depending on the type of heterocycle. Given the ability of the azole‐aurone hybrids to inhibit α‐glucosidase in a parabolic mixed‐type manner, the values of apparent inhibition constants were calculated. The molecular docking simulations revealed that, in addition to the dominant role of the aurone moiety, the substituted heterocyclic part also contributes to the stabilization of the inhibitor within the enzyme active site.